Nanostructured Light Guide Sensors of the Solvents’ Vapors in Atmosphere - Fedorovich, Novikov Alexander (Innovations in Science and Technology Vol. 1, 2021)
Chemical sensors of solvents’ vapors based on different light guides (integrated- and fiber-optics) were designed and tested. The vapor sensitive substances were introduced into nano-scale porous outer layers of the light guide substrate/core. A substrate/core material used was phase separated silicate glass or polyester polymer.